Environmental Governance in The Division of Roles International Institutions and Government Institutions in African Countries - Mariette Tsitohery; Colette Zafimahova (Journal of Management and Administration Provision, 2022)
The study is aims to assess the division of roles between international and government institutions in promoting sustainable development in the region. The research employs a mixed-methods approach, including a survey of experts, a review of existing literature, and an analysis of case studies, to gain a comprehensive understanding of the current state of environmental governance in African countries. The findings of the study suggest that the division of roles between international and government institutions is a complex and dynamic process that is shaped by a variety of factors, including the level of economic development, the political context, and the capacities of different actors. The current state of environmental governance in African countries is influenced by a range of challenges, including limited resources, weak institutions, and a lack of political will to prioritize environmental protection. However, the study also identifies a number of opportunities for improving environmental governance in the region. These include greater collaboration between international and government institutions, the development of more effective policies and initiatives, and increased investment in environmental protection and sustainable development. Overall, the research highlights the importance of taking a comprehensive and integrated approach to environmental governance in African countries, and underscores the need for continued efforts to balance economic growth and environmental protection in the region. The study provides valuable insights for policy makers, international institutions, and government institutions, and will inform future efforts to promote sustainable development in Africa.